ANALISIS FINANSIAL USAHA KERAJINAN KALIGRAFI KULIT KAMBING DI KECAMATAN SUKOHARJO KABUPATEN SUKOHARJO - Shanti Emawati; Endang Siti Rahayu; Sutrisna Hadi Purnomo; Ayu Intan Sari; Endang Tri Rahayu; Winny Swastike (Universitas Sebelas Maret, 2016)
The research was conducted to determine the feasibility of financial on SMEs calligraphy goat leather in Sukoharjo District. Research was done from January 6 to March 26, 2015 in located in Sukoharjo District. Survey methods was done to collect primary data from respondents and secondary data from related institution. Census method was applied to sellect respondents. Criteria used to analyze the feasibility of financial on SMEs calligraphy goat leather were consisted of Benefit Cost Ratio (BCR), Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Period (PPC), based on 6 years investment and 12% annual discount factor. The result showed that based on NPV, IRR, BCR and payback period analysis, the most feasible of respondents was achieved on scale of 3 with value of NPV = Rp. 434,852,752.00, IRR = 37.93%, BCR = 1.92, followed by on scale of 2 with value of NPV = Rp. 76,481,554.00, IRR = 22.51%, BCR = 1.37 and on scale of 1 with value of NPV = Rp. 34,883,505.00, IRR = 20.41% dan BCR = 1.28. In term of payback period, respondents who had SMEs calligraphy goat leather on scale of 3 were able to return the investment during 2.39 years while on scale of 2 and on scale of 1 were 3.72 and 3.79 years, respectively.